The The Influence Of The Existence Of A Cocoa Plantation Company (Theobroma cacao L) On The Socio-Economic Condition Of The Workers Of PT Sumber Daya Wahana - GRACIA IMMANUELA LEKATOMPESSY; LEUNARD ONISIVORUS KAKISINA; FELECIA PETROSINA ADAM (Cita Konsultindo Research Center, 2022)
This research related to the Effect of the Existence of a Cocoa Plantation Company (Theobroma cacao L) on the Socio-Economic Condition of the Workers of PT Sumberdaya Wahana, has been carried out at PT Sumberdaya Wahana which is located in Siatele Village, North Seram District, Central Maluku Regency, Maluku Province for approximately one year. month long. This study aims to determine whether or not the influence given by PT Sumberdaya Wahana to the workforce in terms of socio-economic aspects. This research uses quantitative and qualitative methods. Observational variables in this study include the existence of companies as independent variables, income variables, ownership of living facilities, education, and health as dependent variables. The results of this study indicate that the T-Statistic test of the income variable (5.045), the ownership variable of living facilities (1.987), the education variable (6.050) and the health variable (3.885) and the value of the P-Value of each variable is <0.005. Therefore, it can be concluded that there is an influence of the existence of a Cocoa plantation company (Theobroma cacao L) on the socio-economic conditions of PT Sumberdaya Wahana's workforce. Keywords: Socio-economic; Labor; Company